Hubungan Asupan Protein Dan Asupan Kalium Terhadap KadarKreatinin Pasien Gagal Ginjal Kronik Di Rsud KabupatenSukoharjo - Dewi Rustiana, Eka, Nur Latifah Mardiyati, S.Gz., MS, Dyah Widowati, SKM (2015)
Background: Chronic renal failure patients need to restrict their protein intake because the occurrence of renal dysfunction such as uremia. Chronic renal failure patients are also given with low in potassium diet as usually the patients experience hyperpotassium that is related with oliguri (reduction in urine volume), metabolic state, or medicines that contain potassium. Purpose: To investigate the correlation between protein and potassium intakes and creatinin level in chronic renal failure patients at the Region Hospital of Sukoharjo. Research methode: This research was an observasional study with cross- sectional design. Responden were 30 outpatients of chorinc renal failure, who were selected thruogh consecutive sampling technique. Statical analize used pearson product moment tests. Result: The average of protein intake was 33,13 gram,while the average of potassium intake was 977,9 milligram. Based on the pearson product moment tests there was relationship between protein intake and creatinin level (p value 0,329) and relationship between potassium intake and creatinin level (p value 0,280). Conclusion: There was no correlation between protein and potassium intakes and creatinin level in chronic renal failure outpatients at Region Hospital of Sukoharjo.